Evolutionary enhancement of Zika virus infectivity in Aedes aegypti mosquitoes - Liu, Yang; Liu, Jianying; Du, Senyan; Shan, Chao; Nie, Kaixiao; Zhang, Rudian; Li, Xiao-Feng; Zhang, Renli; Wang, Tao; Qin, Cheng-Feng; Wang, Penghua; Shi, Pei-Yong; et al. (Nature (London), 2017)
A mutation that increases the secretion of Zika virus non-structural protein 1 (NS1) in infected hosts enhances the ability of the virus to infect its mosquito vector Aedes aegypti and might have contributed to the recent Zika epidemic. Mutation enhances Zika infectivity in mosquitoes Several flaviviruses, such as dengue fever virus and Zika virus, are transmitted by mosquitos. Gong Cheng and colleagues have previously shown that the acquisition of flaviviruses by mosquitoes can be influenced by the flavivirus non-structural protein 1 (NS1), which can be secreted into the serum of an infected host and acquired by the mosquitoes together with the virus. Here, the authors show that such a mechanism also operates to enhance the acquisition of Zika virus (ZIKV) infection by its mosquito vector A. aegypti . The authors identify a mutation in NS1 that enhances its secretion and hence serves to increase mosquito acquisition of the virus. In a survey of NS1 proteins from Asian isolates of ZIKV, the authors also find that the mutation is observed in all isolates collected after 2013. The authors speculate that this mutation in NS1 may have contributed to the rapid spread of the recent epidemic. Zika virus (ZIKV) remained obscure until the recent explosive outbreaks in French Polynesia (2013–2014) and South America (2015–2016) 1 , 2 , 3 . Phylogenetic studies have shown that ZIKV has evolved into African and Asian lineages. The Asian lineage of ZIKV was responsible for the recent epidemics in the Americas 1 , 3 . However, the underlying mechanisms through which ZIKV rapidly and explosively spread from Asia to the Americas are unclear. Non-structural protein 1 (NS1) facilitates flavivirus acquisition by mosquitoes from an infected mammalian host and subsequently enhances viral prevalence in mosquitoes 4 . Here we show that NS1 antigenaemia determines ZIKV infectivity in its mosquito vector Aedes aegypti , which acquires ZIKV via a blood meal. Clinical isolates from the most recent outbreak in the Americas were much more infectious in mosquitoes than the FSS13025 strain, which was isolated in Cambodia in 2010. Further analyses showed that these epidemic strains have higher NS1 antigenaemia than the FSS13025 strain because of an alanine-to-valine amino acid substitution at residue 188 in NS1. ZIKV infectivity was enhanced by this amino acid substitution in the ZIKV FSS13025 strain in mosquitoes that acquired ZIKV from a viraemic C57BL/6 mouse deficient in type I and II interferon (IFN) receptors (AG6 mouse). Our results reveal that ZIKV evolved to acquire a spontaneous mutation in its NS1 protein, resulting in increased NS1 antigenaemia. Enhancement of NS1 antigenaemia in infected hosts promotes ZIKV infectivity and prevalence in mosquitoes, which could have facilitated transmission during recent ZIKV epidemics.